PENDAMPINGAN PEMASARAN DAN PROMOSI PADA USAHA TAS ANYAMAN DI DESA KARANGSONO KABUPATEN JEMBER - Tri Palupi Robustin (JURNAL PENGABDIAN MASYARAKAT (JPM), 2022)
UMKM on the other hand also have weaknesses one of which is in terms of marketing and promoting products, this is because the owner of UMKM is from among the villagers who still do not understand the science of marketing, all activities are sometimes still traditional. The problem faced by Siti Nailul Fauziyah's woven bag business is that product promotion has not been done to the maximum, business owners only promote bags on whatsapp. In addition, marketing activities are also still limited to only producing products if there is a message, if no one messages then do not make bags. competition. This is what causes this woven bag is not yet widely known by the public, so promotion using various media needs to be done. This community service provides assistance in the marketing and promotion of products. Promotional and marketing assistance aims to introduce woven bag products to the wider community so as to increase the sales of woven bags.